AN ATTEMPT TO IDENTIFY CULTURAL ECOSYSTEM SERVICES AND RELATED LAND USE TYPES IN RURAL AREAS UNDER URBANIZATION - Xuehui Sun (Zibeline International, 2021)
Cultural Ecosystem Services (CES) play an important role in socio-natural ecosystems. Assessment of CES in rural areas is crucial for development planning and decision-making. However, assessment of CES at the local scale and, in particular, rural areas remain under-researched. In order to reveal the importance of different kinds of CES and the related land uses perceived by the rural residents, a simplified tick-scoring method was developed and tested in a case study of four villages in Shandong Province, China. This method poses CES questions and seeks answers about corresponding land use types in a questionnaire form that is accessible and useful to village residents. Furthermore, the important categories of CES and related land use types were identified and ranked based on the questionnaire. The results showed that ecological culture and aesthetic services ranked in the top two of twelve CES categories, while scenic spots/mountains, forests, and lakes/rivers/reservoirs scored for multiple CES and attained higher than average CES scores. Overall, the simplified method is practical to understand the perspectives of rural residents on the important CES and related landscapes. The established approach shed lights on CES assessment and management improvement at local scale of rural areas under different socio-environmental contexts in China and elsewhere.